Research on RTCWeb and Its Merging with IMS - Lifeng Le; Jin Peng; Xiaodong Duan (Dianxin kexue)
RTCWeb is a key technology to realize free plug-in web client. Compared with traditional client, RTCWeb client enables more convenient operation, more flexible development, and detachment from the operating system and platform. It is a better choice for service developers, network operators and terminal users. This paper firstly introduced RTCWeb's communication model and key technologies, then proposed the conception of RTCWeb's merging with IMS and gave the specific solutions under the conception, finally gave a summery and a prospect for future evolution of IMS based RTCWeb system.